Solid-phase denitrification and denitritation of swine manure-contaminated waters: Bioreactor performance and microbial community profiles. Issue 1 (February 2023) - Nia, Ali Ekhlasi; Khaledi, Kharazm; Predicala, Bernardo; Nemati, Mehdi
Abstract: Waste streams from livestock facilities contribute to water contamination by nitrogenous compounds and a feasible approach for their treatment is needed. In this work, a microbial culture, originally developed for anoxic biodegradation of naphthenic acids, was used in woodchip bioreactors to evaluate denitrification and denitritation in medium simulating livestock wastewaters. Effects of nitrate and nitrite concentrations (10–150 mg L −1 ), loading rate (0.8–2000.2 mg L −1 day −1 ), manure content (0–10%), and residence time (0.04–11.26 day) on the performance of bioreactors operated with nitrate, nitrite or their mixture were investigated. The highest nitrate removal rates for nitrate alone were achieved at loading rates of 1000–1500 mg L −1 day −1 and 9–10% manure (removal rate ≥ 400 mg L −1 day −1 ), and for nitrate in mixture at 775–1150 mg L −1 day −1 and 7–10% manure (removal rate ≥ 350 mg L −1 day −1 ). For nitrite alone, these were 1000–1500 mg L −1 day −1 and 0–2% manure (removal rate ≥500 mg L −1 day −1 ) and 600–850 mg L −1 day −1 and 5–10% manure (removal rate ≥ 300 mg L −1 day −1 ) for nitrite in mixture. High nitrite concentration (75–100 mg L −1 ) negatively impacted its removal rate in mixture with nitrate or alone. Bioreactors microbial profiles were different from each other and from the stock cultures. Cloacimonetes, Firmicutes, and Proteobacteria phyla were prevalent in all bioreactors, but Bacteroidetes was seen only in the nitrate and nitrite bioreactors. At the class level, Candidatus cloacamonas, Thiomicrospira and Pseudomonas were seen in all bioreactors but Acidovorax and Comamonas were significant only in the nitrite bioreactor. Graphical Abstract: ga1 Highlights: Culture developed with naphthenic acids was effective in solid phase denitrification. Denitrification and denitritation rates depended on loading rate and manure content. Removal rates for individual compounds were higher than those in mixture. High nitrite concentration negatively impacted its removal rate. Carbon source and nitrogenous compound affected the bioreactors microbial profiles.